Biochemistry and Future Perspectives of Antibiotic Resistance: An Eye on Active Natural Products - Giulia Caioni; Carolina Pérez Reyes; Davide Laurenti; Carmen Chiaradia; Enrico Dainese; Roberto Mattioli; Daniel Di Risola; Eleonora Santavicca; Antonio Francioso (Antibiotics)
Antibiotic resistance poses a serious threat to the current healthcare system, negatively impacting the effectiveness of many antimicrobial treatments. The situation is exacerbated by the widespread overuse and abuse of available antibiotics, accelerating the evolution of resistance. Thus, there is an urgent need for novel approaches to therapy to overcome established resistance mechanisms. Plants produce molecules capable of inhibiting bacterial growth in various ways, offering promising paths for the development of alternative antibiotic medicine. This review emphasizes the necessity of research efforts on plant-derived chemicals in the hopes of finding and creating novel drugs that can successfully target resistant bacterial populations. Investigating these natural chemicals allows us to improve our knowledge of novel antimicrobial pathways and also expands our antibacterial repertoire with novel molecules. Simultaneously, it is still necessary to utilize present antibiotics sparingly; prudent prescribing practices must be encouraged to extend the effectiveness of current medications. The combination of innovative drug research and responsible drug usage offers an integrated strategy for managing the antibiotic resistance challenge.